External and internal distractions of the healthcare worker during the working day: Bibliographic review - Gaitán-Gómez, Olga Lucía (2023)
Objective: To analyze the scientific evidence available on the external and internal distractions of the health worker and worker during the workday. Method: Bibliographic review in five databases between the years 2001 and 2021. Main results: External (electronic devices, noise pollution) and internal (anxiety, physiological needs) distractions with a greater presence in the work environment that have as a consequence errors in the execution of procedures, delays in the provision of the service and influence on work performance. General conclusion: The scientific evidence found in this phenomenon was scarce. The most reported external distractions were the use of electronic devices and noise pollution, while internal distractions covered emotional aspects and biological needs. Few studies propose strategies to mitigate their impact, which is why they are invited to unify them in a single intervention and thus enhance their effect.